Single and Sequential Applications of Anthem Maxx, Solstice, Acuron, Balance Flexx, Corvus, Halex GT, Verdict, Sharpen, Glyphosate, and Atrazine in Irrigated Corn - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2017)
A study was initiated near Garden City, KS, in 2016, comparing the weed control of several herbicide treatments and their sequential application for weed control in irrigated corn. Quinoa and common sunflower control was excellent. All sequential herbicide treatments provided excellent control of kochia, velvetleaf, Palmer amaranth, and green foxtail. Single applications at the V4 stage, although still good, showed a reduced level of Palmer amaranth and green foxtail control compared to sequential treatments.
Keywords: Application timings; residual control